Determination of Earnings Quality and Firm Value: New Evidence from Indonesian Non-financial Companies - Ellin .; Erna Wati (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2023)
This research aims to determine the factors affecting earnings quality and firm value empirically. Two theories underlie the conceptual framework of this research, namely agency theory and signaling theory. Agency conflicts arise due to conflicts of interest and information asymmetry between principals as users of information and agents as providers of information. Then, the emergence of signal theory acts as a moral reason for companies to send signals to the market to reduce information asymmetry between agents and principals by reporting on the company's operating and financial performance. The statistical population of this research consists of all non-financial companies listed on the Indonesia Stock Exchange covering the period of 2017-2020, giving 1.735 and 1.727 observations data for each dependent variable. This study employs multiple linear regression methods to test and analyze the data. The findings show a significant relationship between growth, Earnings Quality (EQ), and Firm Value (FV). Firm size, cash to current assets, current debt to total assets, listing age, market capitalization, and earnings management have no significant influence on EQ but significant on FV. The managerial capability only has a significant impact on EQ. Furthermore, the working capital ratio, earnings per share, firm age, price earnings ratio, and CSR award do not affect EQ and FV. The novelty of this research is to acumen the best factor affecting earnings quality and firm value.